2020
DOI: 10.1007/s11119-020-09723-5
|View full text |Cite
|
Sign up to set email alerts
|

Status quo of adoption of precision agriculture enabling technologies in Swiss plant production

Abstract: This paper presents the state of application of Precision Agricultural enabling Technology (PAT) in Swiss farms as an example for small-scale, highly mechanised Central European agriculture. Furthermore, correlations between farm and farmers’ characteristics and technology adoption were evaluated. Being part of a comprehensive and representative study assessing the state of mechanisation and automation in Swiss agriculture, this paper focuses on the adoption of Driver Assistance Systems (DAS) and activities in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 26 publications
2
42
0
6
Order By: Relevance
“…Interestingly, our results further showed that farmers using tie stall barns adopted less technology, both implemented and new, compared to farmers using loose housing systems, likely because many technologies do not bring an added value in tie stall barns, where cows cannot express their behavior freely. The finding that the zone correlated with technology adoption was to be expected and confirms the results of a recent study on the adoption of precision agricultural technologies on Swiss crop farms (Groher et al, 2020). Mountain farms in particular often generate less income (FSO, 2019b) and have to cope with difficult production conditions, which may explain the strong negative correlation on new technology adoption.…”
Section: Farm and Farmers' Characteristicssupporting
confidence: 85%
“…Interestingly, our results further showed that farmers using tie stall barns adopted less technology, both implemented and new, compared to farmers using loose housing systems, likely because many technologies do not bring an added value in tie stall barns, where cows cannot express their behavior freely. The finding that the zone correlated with technology adoption was to be expected and confirms the results of a recent study on the adoption of precision agricultural technologies on Swiss crop farms (Groher et al, 2020). Mountain farms in particular often generate less income (FSO, 2019b) and have to cope with difficult production conditions, which may explain the strong negative correlation on new technology adoption.…”
Section: Farm and Farmers' Characteristicssupporting
confidence: 85%
“…It is believed that crop production is significantly affected by the terrain features studied in the phytogeomorphological mechanism [16]. The evolution of the phytogeomorphological mechanism is due to the realizationthat the hydrological factors of farmland are controlled by geomorphic components [17].The proliferation of various satellite navigation systems has further boosted the adoption of precision agriculture [18]. Adopting such a navigation system helps localize an appropriate location of the agricultural land suitable for production.…”
Section: Precision Agriculturementioning
confidence: 99%
“…Usage of various controllers, actuators, and sensors further offers relevantwater supply statistics for better irrigation management. To effectively operational, PA demands the use of progressive technologies, i.e., usage of sensors [10], precision farming software [11], connectivity protocols [12], and location monitoring tools [13]. Irrespective of PA's known benefits, it is still yet to get a discloser about the research progress regarding more insights over challenging state of farming, minimal resource waste, identifying the unique pattern of production or risk.…”
Section: Introductionmentioning
confidence: 99%
“…This lack of a clear and shared definition makes it difficult to study the adoption [ 3 ]. Moreover, the factors affecting the adoption rates depend on the type of PA technologies [ 5 ], which are many, such as remote sensing (including soil sensing, satellite remote sensing and proximal remote sensing), yield monitoring and mapping, variable rate technology, grid or zone soil sampling [ 3 , 47 ]. However, the International Society for precision agriculture (ISPA) recently recognized the following as the official definition of PA: “ Precision Agriculture is a management strategy that gathers, processes and analyzes temporal, spatial and individual data and combines it with other information to support management decisions according to estimated variability for improved resource use efficiency, productivity, quality, profitability and sustainability of agricultural production ” [ 48 ].…”
Section: Related Workmentioning
confidence: 99%